Experimental and numerical analysis of deformation behaviour of tunnels under static loading conditions. (August 2022) - Kumar, Parvesh; Kumar Shrivastava, Amit
Abstract: The constant growth of cities has led to a shortage of land in metro areas as a result; numerous transportation issues must be addressed. The design of underground structures has proved to be very successful in overcoming these issues, as they have solved numerous traffic problems in major cities. However, due to their heterogeneous behaviour, these underground structures are extremely vulnerable to damage or failure. As a result, it is very important to keep underground structures secure under various loading conditions. This research aims to determine the deformation behaviour of single and twin tunnels under static loading conditions. The present study is divided into two steps. Firstly, laboratory experiments are carried out on small-scale physical simulated tunnels models. Secondly, numerical simulation of physical simulated tunnel models was carried out to determine the deformation that occurs at various points in the tunnel model. Then the results obtained from the experimental and numerical study are compared and validated. From the results, it is observed that experimental testing results are in good agreement with numerical modelling results. It is also observed that if the parameters are well selected for numerical analysis, it can be an easy and less time-consuming method for finding out strength and deformation behaviour for analysis and design of the tunnel. Therefore it can be concluded that the testing methodology which is proposed in this study can be used for the safe and economical design of both single and twin tunnels that are subjected to static loading conditions.